Knowledge Management and Knowledge Management Systems: Conceptual Foundations - SHARMA, DR. DINESH (The journal of contemporary issues in business and government, 2021)
Information is a common and abstract notion defined epistemological conversation in western philosophy since the Greek Classical era. However, there has been mounting attention in the treatment of in sequence as an important organizational tool in recent years. According to the interest in organizational information and knowledge management (KM), there searchers have begun to promote a class of information systems, referred to as Knowledge management system (KMS). KMS is to support knowledge creation, transfer and submission in organizations. Management of information and consciousness is a dynamic subject with several facets. So efficient development and implementation for KMS a foundation is needed in several rich read more Literatures.KMS Research and Development to be reliable should maintain and build on substantial writing which exists in different but related fields. This paper analyses and interprets the literature on knowledge management in a variety of fields with an eye to identifying key study areas. Comprehensive method vision of information management in the association focusing on the possible Knowledge arrangement in that phase, knowledge is outlined in this paper. Building on the reviewing literature and evaluating knowledge management methods, discussion is done on a variety of relevant research issues related to the processes of knowledge management and the role of IT in support in those processes.